2010
DOI: 10.1089/vbz.2009.0136
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of St. Louis Encephalitis Virus in Culex quinquefasciatus (Diptera: Culicidae) in Córdoba, Argentina

Abstract: Arbovirus vector transmission is interrupted when vector abundance decreases or disappears in temperate regions during the winter season. Although the primary overwintering mechanism for many arboviruses in nature remains unknown, vertical transmission is one potential mechanism. Vertical transmission functions as an overwintering mechanism for St. Louis encephalitis virus (SLEV) in temperate areas of Argentina, where SLEV is endemic. The aim of this project was to detect vertical transmission of SLEV in Culex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…In reviewing the literature on laboratory infections we noted that in nearly all studies, the infective blood meal was given to nulliparous mosquitoes [11], [12] and detection of virus was limited to the offspring of the first gonotrophic cycle, whereas, when studies continued through subsequent cycles, rates of vertical transmission were found much higher [11], [24], [25]. We speculated that the difference could be attributable to two factors:(i) the first batch of eggs is laid several days before virus has begun rapid replication after passing via the gut wall into the hemolymph, and/or (ii) the enormous increase in the volume of the ovaries during oogenesis might increase its permeability to virus.…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing the literature on laboratory infections we noted that in nearly all studies, the infective blood meal was given to nulliparous mosquitoes [11], [12] and detection of virus was limited to the offspring of the first gonotrophic cycle, whereas, when studies continued through subsequent cycles, rates of vertical transmission were found much higher [11], [24], [25]. We speculated that the difference could be attributable to two factors:(i) the first batch of eggs is laid several days before virus has begun rapid replication after passing via the gut wall into the hemolymph, and/or (ii) the enormous increase in the volume of the ovaries during oogenesis might increase its permeability to virus.…”
Section: Introductionmentioning
confidence: 99%
“…Culex mosquitoe abundance decreases drastically during winter, so vector transmission to vertebrates would not be maintained during this season. Supporting endemicity of SLEV, Flores et al [21] detected vertical transmission of SLEV genotype V in local Culex mosquito populations under laboratory conditions. We believe that this mechanism would satisfactory explain the maintenance of some viral variants until the next favorable season for mosquito vector proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…The St. Louis encephalitis virus is the etiological agent of St. Louis encephalitis and is a member of the Japanese encephalitis antigenic complex. It was first detected in 1933 during an outbreak of human encephalitis in St. Louis in the US State Missouri (Auguste et al 2009;Flores et al 2010;Rodrigues et al 2010). Today, the virus is found all over the USA and Canada as well as Central and South America (Diaz et al 2006;Pires and Gleiser 2010).…”
Section: Flaviviridae: Flavivirusmentioning
confidence: 99%
“…The largest outbreak of SLEV among humans so far was in 2005 in Argentina (Diaz et al 2006). The first detection of SLEV in Argentina was in 1957 (Flores et al 2010). Studies have indicated Cx.…”
Section: Flaviviridae: Flavivirusmentioning
confidence: 99%